Adapting English Teaching to Industry Needs: An Instructional Perspective of Vocational High School Teachers - Royyani, Nauroh; Gozali, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
English proficiency is essential in vocational education as it equips students with the communication skills needed in industrial workplaces. However, English instruction in many vocational schools remains general and does not address the specific communication demands of different professions, creating a gap between classroom practices and workplace expectations. This study explores how English teachers in a vocational high school adapt their instructional practices and how institutional leadership supports these efforts. Using a qualitative case study, data were collected through semi-structured interviews with three English teachers and one vice principal of curriculum at a Vocational High School in Indonesia. The findings reveal that teachers employ project-based learning, authentic materials, and role-play to contextualize English instruction, with partial support from curriculum coordination and leadership initiatives. The study concludes that stronger collaboration among teachers, leaders, and industry partners is needed to ensure that vocational English instruction effectively meets workplace communication needs.